PENGARUH CORPORATE GOVERNANCE DAN TIPE INDUSTRI TERHADAP PENGUNGKAPAN KINERJA SOSIAL DAN LINGKUNGAN PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA - Septiana Rahayu; Eko Suyono; Christina Tri Setyorini; Mafudi * (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study haved to analyze the effect corporate governance and type of industry on the corporate social responsibility disclosure. Corporate governance mechanism is used the proportion of independent commissioners, audit committee, institutional ownership and managerial ownership. The population in this study are companies listed on the Indonesian Stock Exchange (BEI) in the year 2012-2014. The number of samples in this study amounted to 132 firm year by purposive sampling method. Based on the results of research and data analysis using multiple linear regression showed that: 1) the proportion of independent commissioners positive influence on the CSR disclosure, 2) the audit committee positive influence on the CSR disclosure, 3) institutional ownership positive influence on the CSR disclosure, 4) managerial ownership had no influence on the CSR disclosure, and 5) industrial type variables that influence on the CSR disclosure is agriculture, consumer goods industry, and property and real estate. While the mining sector, basic industry and chemicals, miscellaneous industry, and transportation and infrastructure had no influence to the CSR disclosure.